2017
DOI: 10.1016/j.cbi.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of cadmium and zinc co-exposure in PC12 cells and the underlying mechanism

Abstract: Cadmium (Cd) is a well studied inducer of cellular necrosis and apoptosis. Zinc (Zn) is known to inhibit apoptosis induced by toxicants including Cd both in vitro and in vivo. The mechanism of Zn-mediated protection from Cd-induced cytotoxicity is not established. In this study, we aimed to understand the effects of Zn on Cd-induced cytotoxicity and apoptosis using PC12 cells. Cell viability and DNA fragmentation assays in PC12 cells exposed to Cd and/or Zn revealed that Cd (5 and 10 μmol/L) alone induced sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…However, it was observed that the rats given 2.5 mg/kg BW of cadmium chloride had a significantly fewer WBC compared to the rest of the experimental groups. This could be attributed to the cytotoxic property of this compound [42]. Congruent with our finding, sub chronic treatment with cadmium has been reported to cause leucopenia in wistar rats [43,44].…”
Section: Haematological Profilesupporting
confidence: 86%
“…However, it was observed that the rats given 2.5 mg/kg BW of cadmium chloride had a significantly fewer WBC compared to the rest of the experimental groups. This could be attributed to the cytotoxic property of this compound [42]. Congruent with our finding, sub chronic treatment with cadmium has been reported to cause leucopenia in wistar rats [43,44].…”
Section: Haematological Profilesupporting
confidence: 86%
“…The induction of p53 leads to Cyt c release [ 46 ]. The release of Cyt c activates Caspase-3 [ 10 ]. The activation of Caspase-3 induces apoptosis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excess Pb caused human and animal neurotoxicity, including behavioral deficit in herring gull brains [ 6 ], hippocampus damage and apoptosis in rat adrenal medulla pheochromocytoma cells (PC 12) [ 7 ], oxidative stress and apoptosis in human neuroblastoma cells [ 8 ], and apoptosis in rat brains [ 9 ]. Cadmium (Cd) disrupted mitochondrial membrane integrity and triggered release of mitochondrial proteins cytochrome c (Cyt c) into cytosol, then Cyt c activated Caspase-3, finally apoptosis occurred in PC 12 [ 10 ]. Pb induced apoptosis via mitochondrial pathway in rat proximal tubular cells [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…*P < 0.05 is significant **P < 0.01 is highly significant 2010; Vasiljeva, Berzina, & Remeza, 2011;Vasiljeva, Smirnova, Basova, & Babarykin, 2018). Cadmium induced oxidative damage to the cellular macromolecules and cellular structures (Curcic et al, 2014;Rahman et al, 2017). On another hand, treatment with cadmium and nano-chocolate fortified with zinc improved histopathological lesions and morphometrical changes in the hepatic and testicular tissues induced by cadmium.…”
Section: Discussionmentioning
confidence: 99%